Transcriptomic and Epigenetic Alterations in Dendritic Cells Correspond With Chronic Kidney Disease in Lupus Nephritis - Wardowska, Anna; Komorniczak, Michał; Bułło-Piontecka, Barbara; Dȩbska-Ślizień, M. Alicja; Pikuła, Michał (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) is a serious autoimmune disease with variety of organ manifestations. The most dreadful one, affecting the majority of SLE patients, is kidney manifestation – lupus nephritis (LN). Dendritic cells (DC) are believed to be one of the culprits of immune dysregulation in LN. Flow cytometry analysis was applied to identify the frequency and activity of peripheral blood DCs subpopulations: myeloid and plasmacytoid, in LN patients. Magnetically isolated mDCs and pDCs were subjected to molecular analysis of genes expression, evaluation of global DNA methylation and histone H3 methylation. We observed distinctive features of DCs associated with the stages of nephritis in LN patients. Lower numbers of pDCs were observed in patients with severe LN, while increased costimulatory potential of mDCs was connected with early, mild stage of this disease. IRF1 transcript upregulation was specific for mDCs from total LN patients, while exceptional amounts of IRF1 mRNA was detected in mDCs from severe LN patients. DCs DNA hypermethylation seemed characteristic for severe LN, whereas decrease in H3K4me3 and H3K27me3 marks was significant for early stages of LN. These findings present dendritic cell alterations that may reflect renal involvement in SLE, laying foundations for new strategy of diagnosis and monitoring of LN patients, omitting invasive kidney biopsies.